Knowledge and classification of securities in the business district 2011-2012 Huánuco - Pulgar-Taboada, Victoria M. (2019)
This work is intended as a general tour of the contributions made in recent years by a number of authors who have focused their research activities in the field of knowledge and classification of securities business in the district of Huánuco in the years 2011 and 2012. Not intended to be an exhaustive list of contributions made, but an overview of what has been worked on this comprehensive research and its various ramifications, which is an example of the time course of these studies and the progressive realization on more specific subjects, which have led to a deeper understanding of the cooperative sector, on which there was little work for twenty years.